1915 Campus Day showing group of men posing on wooden boardwalk in front of the Varsity Boathouse, Portage Bay, University of Washington (1915)
The Varsity Boathouse was originally built as the U.S. Coast Guard Life Saving Station on Portage Bay for the 1909 Alaska-Yukon Expedition. Handwritten on verso: 1915 Filed in: UW - Campus Day 1915 Campus Day was an annual event from 1904 to 1934. Students and faculty worked together to clear land and improve the campus, with a break for a communal meal.